2015
DOI: 10.2147/ppa.s80327
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ self-reported adherence to capecitabine on XELOX treatment in metastatic colorectal cancer: findings from a retrospective cohort analysis

Abstract: BackgroundCapecitabine plus oxaliplatin (XELOX) has been established as a first-line treatment for metastatic colorectal cancer. Adherence is particularly important with capecitabine to maintain appropriate curative effect. In this study, we monitored the adherence to capecitabine on XELOX treatment and investigated which factors might decrease compliance.MethodsThe study included 242 consecutive patients who received XELOX treatment for metastatic colorectal cancer between October 2009 and March 2012. Adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…It has been demonstrated that adherence with IV chemotherapy is higher compared to oral agents. In addition, adherence rate of oral agents is significantly lower in patients aged ≥ 80 years compared to that in younger patients [ 23 , 24 ]. Treatment persistence was also found to be low in elderly patients of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that adherence with IV chemotherapy is higher compared to oral agents. In addition, adherence rate of oral agents is significantly lower in patients aged ≥ 80 years compared to that in younger patients [ 23 , 24 ]. Treatment persistence was also found to be low in elderly patients of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found no correlations between sociodemographic or clinical characteristics, perceived intensity of side effects and adherence, which is counterintuitive at first sight but in line with other studies reporting mixed results. 8 , 10 , 12 , 13 , 19 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…OOAs are a last line of treatment for most patients with cancer, and patients could theoretically be taking them until the end of life (Kawakami et al, 2015;Winn et al, 2016). Symptom burden is a primary concern for oncology providers in the management of OOAsincreased symptom burden is a primary reason for patients needing temporary stoppages or dose changes with their OOA regimens (Hall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%